Seismic stratigraphy and structural analysis of the western South Korea Plateau (WSKP), East Sea. (14th October 2015) - Cukur, Deniz; Kim, Seong-Pil; Horozal, Senay; Ryu, Byong-Jae; Kim, Gil-Young; Kong, Gee-Soo
Abstract: The western South Korea Plateau (WSKP), situated on the southwestern part of East Sea, is characterized by rifted continental fragments that were formed in the early phase of back-arc opening. In this work, we analyze multi-channel seismic reflection profiles from the WSKP to document the structural and stratigraphic framework of the area. We also present fault-derived stretching (beta) factors related to the continental rifting along two regional seismic profiles. Our data reveal several graben and half graben subbasins, up to 1300 m thick, bound by N–S trending normal faults. We show that, on the basis of constructed isopach maps, tectonic activity was the main controlling factor on the sedimentation through much of the plateau history. The seismic data reveal that the sedimentation history of the WSKP is characterized by four main phases (Phase 1 to Phase 4; P1–P4) separated by regional unconformities. Rapid extension and subsidence took place at an early stage of P1 leading to the graben and half-graben openings. Volcanic activity was widespread at early times and ∼700 m thick succession of lacustrine and fluvial sediments was deposited. Following P2 (early mid Miocene – latest Miocene), dramatic extension and subsidence changed the lacustrine environment into marine, enabling to the deposition of thick marine sediments (∼750 m) over the subbasins. Extension ceased during P3 (latest Miocene – early Pliocene) and less pronounced subsidence continued. At this time, the sedimentation was uniform over the area and included the cyclic succession of hemipelagic deposits and turbidites which were probably expressed by climatic forcing. P3 was interrupted by regional compression, when normal fault movement was reversed and gentle anticlines formed as a result of inversion. The latter was accompanied by widespread uplift and erosion along the western margin of the plateau, and substantial erosion took place on the crests of the folds. The uplift also shifted the main depocenters of the plateau which were ultimately filled by thick mass-transport deposits during the following phase of P4 (early Pliocene – Holocene). Subsidence has been dominant in the area since the beginning of P4, which was locally interspersed by inversion along the reactivated normal faults. Total upper-crust (βf) and whole-crust extension (βc) estimates in the WSKP show similarities, suggesting that the observed rift structure in WSKP has resulted from uniform pure-shear stretching.